Facial growth - Linden, Frans P. G. M. van der, 1932-; McNamara, James A.; Radlanski, Ralf Johannes; Quintessence Publishing Co.; Dentaurum (Firm) (Berlin : Quintessence Pub. Group ; Ispringen, Germany : Dentaurum, 2004)
'Understanding the factors that determine growth patterns and the causes of variation in facial growth is essential to the practice of clinical orthodontics. Beginning in the seventh week of embryonic development, this volume presents the biologic factors that influence the growth of the craniofacial complex, including odontogenesis and skeletal development. Special attention is given to the role of functional components in skeletal development. Features more than 250 pictures and 12 videos grouped in 6 chapters together with written and spoken text that can be reproduced in six different languages (English, German, Spanish, French, Italian, Portuguese). The final chapter contains 3D animations of embryonic development that can be freely rotated and magnified.'-- Publisher description from website.
Title from disc label
System requirements: Pentium-class processor with 500 MHz; 256 MB RAM; Windows 2000/XP; video card supporting 1024x768 pixels at 16 bit (high) colour; DVD-ROM drive; 50 MB free hard disk space
Includes complete text and soundtrack in English, Spanish, French, German, Italian, and Portuguese
Keywords: Facial Bones -- embryology; Facial Bones -- growth & development; Maxillofacial development